Research on Fretting Fatigue of Tungsten Carbide Coating Based on Strain Energy Density Methods - Xin Zeng; Xiaoxiao Wang; Xuecheng Ping; Renjie Wang; Tao Hu (Archives of Metallurgy and Materials, 2023)
The numerical solutions of stress and strain components on the critical plane of tungsten carbide coating were solved based on the critical plane method in three-dimensional coordinate system, and accordingly three strain energy density parameters (Smith-Watson-Topper, Nita-Ogatta-Kuwabara and Chen parameters) were determined to reveal the fretting fatigue characteristics of tungsten carbide coating. In order to predict the fretting fatigue life based on the strain energy density criterion, the expressions between the strain energy density parameter and the fretting fatigue life was obtained experimentally. After the comparison of the three strain energy parameters, it was found that all three parameters could accurately predict the crack initiation position, but only the Smith-Watson-Topper parameters could accurately predict the crack initiation angle. The effects of cyclic load, normal load and friction coefficient on fretting fatigue damage behaviors were discussed by using the Smith-Watson-Topper criterion. The results show that the fretting fatigue life decreases with the increase of cyclic load; an increase in the normal contact load will cause the Smith-Watson-Topper damage parameters more concentrated at the outer edge of the bridge foot; a decrease in the friction coefficient will increase the Smith-Watson-Topper damage parameters in the middle of the contact surface.